Collected Works of George Grant : Volume 2 (1951-1959) - Grant, George Parkin, 1918-1988 (Book collections on Project MUSE., 2002)
A collection of all the important material from the 1950s when philosopher Geroge Grant did his first teaching and writing at Dalhousie University.